2013
DOI: 10.1371/journal.pone.0055367
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Receiver Responses to Components of Multimodal Signals in Two Foot-Flagging Frog Species

Abstract: Multimodal communication of acoustic and visual signals serves a vital role in the mating system of anuran amphibians. To understand signal evolution and function in multimodal signal design it is critical to test receiver responses to unimodal signal components versus multimodal composite signals. We investigated two anuran species displaying a conspicuous foot-flagging behavior in addition to or in combination with advertisement calls while announcing their signaling sites to conspecifics. To investigate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 44 publications
(72 reference statements)
2
30
0
1
Order By: Relevance
“…To stabilize this name, we herein designate a specimen that is most comparable with the original description as the neotype of Philautus (= Micrixalus) kottigeharensis Rao, 1937. This species was identified as Micrixalus saxicola by Gururaja (2010) and Preininger et al (2013aPreininger et al ( , 2013b, and as Micrixalus aff. saxicola by Preininger et al (2013c).…”
Section: Micrixalus Kottigeharensis (Rao 1937)mentioning
confidence: 99%
See 1 more Smart Citation
“…To stabilize this name, we herein designate a specimen that is most comparable with the original description as the neotype of Philautus (= Micrixalus) kottigeharensis Rao, 1937. This species was identified as Micrixalus saxicola by Gururaja (2010) and Preininger et al (2013aPreininger et al ( , 2013b, and as Micrixalus aff. saxicola by Preininger et al (2013c).…”
Section: Micrixalus Kottigeharensis (Rao 1937)mentioning
confidence: 99%
“…Studies have reported habitat features (Reddy et al, 2002), foot-flagging (Krishna and Krishna, 2006;Malhotra and Davis, 1991;Vasudevan, 2001) and reproductive behaviour (Gururaja, 2010) in Micrixalus species, and a few have specifically dealt with visual and acoustic communication in these frogs (Preininger et al, 2013a(Preininger et al, , 2013b(Preininger et al, , 2013c. However, all of these studies concentrated only on two species, M. fuscus and M. 'saxicola', and there is no information available for other species in the genus.…”
Section: Introductionmentioning
confidence: 99%
“…22 and 23). Prior studies suggest that S. parvus use calls as longer-range advertisement signals, whereas they use foot flags predominantly as close-range signals to other males in competition for breeding sites (22,25). Thus, in this species, acoustic and visual displays are used in concert as a multimodal signal, or at least a simultaneous and/or sequential combination of signals necessary for appropriate intraspecific communication (22,26).…”
mentioning
confidence: 99%
“…Males of some frog species that call near forest streams, for example, show elaborate foot-waving displays [16,17]. These displays are thought to have evolved in response to high levels of acoustic background noise to increase their detection by prospective females.…”
Section: Introductionmentioning
confidence: 99%